2022
DOI: 10.1021/acssuschemeng.2c04092
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Gold Catalysis Using Complexes Recovered from Waste Electronic Equipment

Abstract: Despite the greater awareness of elemental sustainability and the benefits of the circular economy concept, much waste electrical and electronic equipment (WEEE) is still destined for landfill. Effective methods for valorizing this waste within our society are therefore imperative. In this contribution, two gold(III) complexes obtained as recovery products from WEEE and their anion metathesis products were investigated as homogenous catalysts. These four recovery products were successfully applied as catalysts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Interestingly, the residual undeposited solid e-waste still contained precious metals, which could be utilized in further recycling processes. McCarthy et al have recently demonstrated that catalyst recovery must not focus primarily on recovering the metal of interest, but that complexed metal ions recovered from e-waste can also be used as effective homogeneous catalysts for various chemical reactions [26]. The authors showcased this by extracting Au(III) with different complexing agents from old subscriber identity module (SIM) cards using a mild and efficient leaching method (Figure 1c).…”
Section: Catalysts From E-wastementioning
confidence: 99%
“…Interestingly, the residual undeposited solid e-waste still contained precious metals, which could be utilized in further recycling processes. McCarthy et al have recently demonstrated that catalyst recovery must not focus primarily on recovering the metal of interest, but that complexed metal ions recovered from e-waste can also be used as effective homogeneous catalysts for various chemical reactions [26]. The authors showcased this by extracting Au(III) with different complexing agents from old subscriber identity module (SIM) cards using a mild and efficient leaching method (Figure 1c).…”
Section: Catalysts From E-wastementioning
confidence: 99%
“…Utilization of (biomass-based) organic media for noble metal recycling [28][29][30][31][32][33][34][35][36][37][38] seems to offer a paradigm shift towards selective metal dissolution with enhanced sustainability (Figure 1). Recent examples of single noble metal selective dissolution include the use of specific ligands [39][40][41] or conditions.…”
Section: Introductionmentioning
confidence: 99%